Experimental Robotics The 12th International Symposium on Experimental Robotics - Khatib, Oussama.; Khatib, Oussama.; Kumar, Vijay.; Kumar, Vijay.; Sukhatme, Gaurav.; Sukhatme, Gaurav. (Springer Tracts in Advanced Robotics,, 2014)
The International Symposium on Experimental Robotics (ISER) is a series of bi-annual meetings which are organized in a rotating fashion around North America, Europe and Asia/Oceania. The goal of  ISER is to provide a forum for research in robotics that focuses on novelty of theoretical contributions validated by experimental results. The meetings are conceived to bring together, in a small group setting, researchers from around the world who are in the forefront of experimental robotics research. This unique reference presents the latest advances across the various fields of robotics, with ideas that are not only conceived conceptually but also explored experimentally. It collects robotics contributions on the current developments and new directions in the field of experimental robotics, which are based on the papers presented at the 12th ISER held on December 18-21, 2010 in New Delhi and Agra, India.This present twelfth edition of Experimental Robotics edited by Oussama Khatib, Vijay Kumar and Gaurav Sukhatme offers in its eight-chapter volume a collection of a broad range of topics in field and human-centered robotics.                          .